2009
DOI: 10.1111/j.1365-2400.2009.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Movement, social cohesion and site fidelity in adult koi carp, Cyprinus carpio

Abstract: Koi carp is an ornamental variant of the common carp, Cyprinus carpio L., that was introduced to New Zealand in the 1960s and has since become a major aquatic pest. A total of 1265 wild adult koi carp were caught by boat electric fishing, dart tagged and released at multiple sites in the lower Waikato River and associated lakes and wetlands between September 2002 and February 2005. Subsequent recaptures by boat electric fishing and recreational fishing returned 76 koi carp (6% of all tagged fish). Of these, 85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…This is a much higher proportion than reported for similar studies in Australia (8.8%; Stuart & Jones ) and New Zealand (6%; Osborne et al . ). Although these studies were in larger river systems where the likelihood of recapture is expected to be lower, the recapture rate in this study is still considered high as released carp had unimpeded access back to the Murray.…”
Section: Discussionmentioning
confidence: 97%
“…This is a much higher proportion than reported for similar studies in Australia (8.8%; Stuart & Jones ) and New Zealand (6%; Osborne et al . ). Although these studies were in larger river systems where the likelihood of recapture is expected to be lower, the recapture rate in this study is still considered high as released carp had unimpeded access back to the Murray.…”
Section: Discussionmentioning
confidence: 97%
“…Most koi monitored for more than 250 d (89%; N = 38) traveled greater than 5 km during some point in the study. Osborne et al (2009) reported that 85% of dart-tagged koi on the Waikato River had moved less than 5 km. These findings are in complete contrast and emphasize the potential misrepresentation that can result from point-in-time mark-recapture studies (Gowan et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Recent mark-recapture studies of koi in the lower Waikato River indicated that this species variant exhibited little movement (Osborne et al 2009) and high fecundity (Tempero 2004;Tempero et al 2006). Osborne et al (2009) marked 1,265 koi in the lower Waikato River basin and of 76 recaptures (5-1,414 d at liberty) 85% moved less than 5 km.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kirpitchnikov (1999), fully scaled and mirror carp have similar viability, although the latter are less resistant and achieve lower growth rates when reared under unfavourable conditions, whereas leather and especially line carp are less viable even under favourable conditions. Further, coloured Japanese varieties known as nishikigoi (or, somewhat tautologically, koi carp), artificially selected from some domesticated or feral forms (Balon 1995), are also encountered as escapees in the wild (Tempero et al 2006;Osborne et al 2009). Once released into the natural habitat (the wild: sensu Copp et al 2005), domesticated forms of the fully scaled carp may revert over time to feral forms resembling their wild ancestor, although they still differ in a range of behavioural, morphological, physiological and reproductive traits (Balon 1995(Balon , 2006Matsuzaki et al 2009Matsuzaki et al , 2010, and possibly also organoleptic properties (Balon 1974).…”
Section: Originmentioning
confidence: 99%